2022
DOI: 10.1111/jth.15823
|View full text |Cite
|
Sign up to set email alerts
|

Direct oral anticoagulants after bariatric surgery—What is the evidence?

Abstract: Background Obesity is a global epidemic and bariatric surgery is used with increasing frequency to treat its complications. The extent to which bariatric surgery alters the efficacy, safety, and pharmacokinetics of direct oral anticoagulants (DOACs) is unknown. Aims In this review, we summarize the evidence supporting the use of DOACs after bariatric surgery and apply our findings to resolve several clinical cases. Materials & Methods We systematically searched MEDLINE, EMBASE, Cochrane Library, CINAHL and htt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 50 publications
(130 reference statements)
0
6
0
Order By: Relevance
“…In patients with a BMI ≥40 kg/m 2 , a relative risk reduction of 25% for ischemic stroke (adjusted HR, 0.75 [95% CI, 0.64-0.87]; P <0.001), 57% for significant bleeding (adjusted HR, 0.43 [95% CI, 0.20-0.94]; P <0.001), and 34% for all-cause mortality (adjusted HR, 0.66 [95% CI, 0.56-0.77]; P <0.001) was observed with DOACs compared with warfarin. Although case reports exist that demonstrate expected factor Xa trough levels in patients taking a DOAC who undergo bariatric surgery, a meta-analysis of cohort studies, case series, and case reports has shown that 42% of patients who have undergone bariatric surgery had peak drug levels below the expected range. 6,7 Patients who have undergone bariatric surgery are not well represented in any of the major trials comparing DOACs with warfarin, and few observational data support DOAC use in this population. Warfarin’s therapeutic effect can be routinely monitored.…”
Section: Af and Specific Patient Groupsmentioning
confidence: 99%
“…In patients with a BMI ≥40 kg/m 2 , a relative risk reduction of 25% for ischemic stroke (adjusted HR, 0.75 [95% CI, 0.64-0.87]; P <0.001), 57% for significant bleeding (adjusted HR, 0.43 [95% CI, 0.20-0.94]; P <0.001), and 34% for all-cause mortality (adjusted HR, 0.66 [95% CI, 0.56-0.77]; P <0.001) was observed with DOACs compared with warfarin. Although case reports exist that demonstrate expected factor Xa trough levels in patients taking a DOAC who undergo bariatric surgery, a meta-analysis of cohort studies, case series, and case reports has shown that 42% of patients who have undergone bariatric surgery had peak drug levels below the expected range. 6,7 Patients who have undergone bariatric surgery are not well represented in any of the major trials comparing DOACs with warfarin, and few observational data support DOAC use in this population. Warfarin’s therapeutic effect can be routinely monitored.…”
Section: Af and Specific Patient Groupsmentioning
confidence: 99%
“…There is little evidence regarding the use of DOAC in these cases, but overall, its use is preferably avoided as first-line anticoagulation in patients who have undergone these types of surgeries until more data are available. 37 38 In addition, DOACs are not effective in APS. Studies suggest a higher thrombotic risk in APS patients treated with DOACs.…”
Section: Discussionmentioning
confidence: 99%
“…33 However, there could be a substantial risk of malabsorption after gastric bypass, especially with rivaroxaban. [34][35][36] Some guidelines suggest that DOAC should not be used for treatment or prevention of VTE in the acute setting after bariatric surgery. 37…”
Section: Direct-acting Oral Anticoagulantsmentioning
confidence: 99%
“…More recently, a randomised controlled trial compared 1 week and 4 weeks of rivaroxaban (10 mg once daily) after bariatric surgery and found only one VTE (0.4%), without differences between the short and extended protocol 33 . However, there could be a substantial risk of malabsorption after gastric bypass, especially with rivaroxaban 34–36 . Some guidelines suggest that DOAC should not be used for treatment or prevention of VTE in the acute setting after bariatric surgery 37 …”
Section: Rationalementioning
confidence: 99%